2017
DOI: 10.1097/md.0000000000008940
|View full text |Cite
|
Sign up to set email alerts
|

The improvement of dry eye after cataract surgery by intraoperative using ophthalmic viscosurgical devices on the surface of cornea

Abstract: Backgroud:This study aimed to investigate the protective effect of intraoperative used hydroxypropyl methylcellulose (HPMC 2%) on the ocular surface after cataract surgery.Methods:A total of 149 eyes (149 patients) diagnosed with age-related cataract, age 69.19 ± 9.74 years, were enrolled in this prospective, parallel-design, continuous, randomised controlled study. Patients were randomly assigned to receive HPMC 2% (study group) or balanced salt solution (control group) during the surgery to moisturize the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 22 publications
1
30
0
Order By: Relevance
“…Since the objective findings do not always correlate with the subjective symptoms, subclinical KCS can be overlooked, which then gets worse after the operation. Previous publications have shown that cataract surgery can worsen existing preoperative KCS [12]. It is therefore important to analyse how the cataract operation itself influences the tear film on the ocular surface.…”
Section: Discussionmentioning
confidence: 99%
“…Since the objective findings do not always correlate with the subjective symptoms, subclinical KCS can be overlooked, which then gets worse after the operation. Previous publications have shown that cataract surgery can worsen existing preoperative KCS [12]. It is therefore important to analyse how the cataract operation itself influences the tear film on the ocular surface.…”
Section: Discussionmentioning
confidence: 99%
“…As such there is potential for damage to the corneal and conjunctival surface. He et al., 72 in a prospective randomized controlled study (RCT) of 149 patients, compared the intra-operative use of hydroxypropyl methylcellulose (HPMC) 2% or balanced salt solution (BSS) to coat the ocular surface during cataract surgery and documented that when using HPMC 2% intra-operatively, tear film assessment measures (Schirmer I test) and ocular surface health (fluorescein staining) were better in some patient groups, especially those with DED before surgery and patients whose surgical time was protracted. 72 Similarly, Yusufu et al., 73 in a prospective interventional case series of 60 eyes, documented reduced DED symptoms and better TBUT with the intra-operative use of HPMC 2% compared to BSS.…”
Section: The Pathophysiology Of Cataract Surgery Associated Dedmentioning
confidence: 99%
“…As discussed above, there are several intra-operative factors that may be important in the pathophysiology of cataract surgery-induced iatrogenic DED including corneal nerve damage secondary to surgical incisions; the potentially toxic effects of povidone-iodine and topical anaesthetic drops on the ocular surface; repeated ocular surface drying/irrigation; phototoxicity; and direct ocular surface trauma. 51 , 55 78 , 83 85 The cataract surgeon needs to be mindful of these factors when operating on patients, especially when a patient has any pre-existing DED 17 , 18 , 47 , 48 , 97 ( Table 1 ).…”
Section: Considerations Of the Management Of Cataract Surgery Associamentioning
confidence: 99%
See 1 more Smart Citation
“… 6 , 7 , 8 Surgical procedures like cataract surgery cause denervation of the cornea, which results in impaired epithelial wound healing, increased epithelial permeability, decreased epithelial metabolic activity, and loss of cytoskeletal structures associated with cellular adhesion. The incidence of dry eye syndrome among patients undergoing cataract surgery has been shown to be dependent on a host of factors including type of procedure, type of ophthalmic solution being used 9 , intraoperative medication 10 , coexistent systemic disorders 11 , operating microscope light exposure and cumulative dissipated energy (CDE) used during the procedure 12 , and time since surgery. 13 …”
Section: Introductionmentioning
confidence: 99%